Women's empowerment, development and gender equality plan, 2013-2016 women's edge plan. (Philippine Commission on Women, 2014)
The Women's Empowerment, Development and Gender Equality Plan 2013-2016 or the Women's Edge Plan is the gender equality guiding plan of the Philippine Development Plan 2011-2016. It is the 2nd Framework Plan for Women & the second time-slice plan of the Philippine Plan for Gender-Responsive Development (PPGD 1995-2025). The 1st Framework Plan for Women, the first time-slice plan of the PPGD 1995-2015 was implemented during the period 2004-2010.